Control Structure of Garba Formation Through Petrography Analysis in Tanjung Beringin, South OKU Regency, South Sumatra - Putra, Ridho Widyantama; Nasution, Frillia; Putri, Nurlita; Alfath, Rahmat (UIR PRESS, 2016)
The study area is the village of Tanjung Beringin carefully situations, South OKU Regency, which is included within the Subpalembang Basin  with the dominant lithology is granite. Granite in this area has a diversity of grain size and mineral composition, in the southern part of the study area the size of the mineral feldspar is greater than the granite in the northern part, where the granite in this section contains plagioclase and quartz dominant, and it was bigger than the other minerals, Granite on the area carefully situations are the result of the appointment that occurs due to the compression phase at the end of the Late Jurassic until Late Cretaceous. Fracture growing on granite have a general direction Northeast equivalent to tectonic compression Miocene - Now, the presence of other directional sharpness is secondary sharpness formed by the collision between the rocks. Fractures that develops is the path where the discharge of magma to the formation of granite with different characteristics. In petrographic analysis porphyritic texture is thriving and there are indications of alteration process in the presence of alteration minerals such as chlorite and quartz vein.